Gym-Related Injuries and its Prevention and Treatment Strategies - Ba, Yuyao; Du, Daixin; Hu, Jiefu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In contemporary society, health and fitness have received more and more attention and become an important venue for the public to pursue physical health and good posture. However, in the actual fitness exercise, because most exercisers lack the correct cognition of their own athletic ability, physical condition and movement norms, in the daily exercise process, there will often be unpredictable sports injuries. At the same time, the lack of professional knowledge in the self-treatment of injury leads to the aggravation of injury, which has a negative impact on all aspects of daily life such as my study and work. However, current research on fitness related sports injuries is relatively limited. Through the analysis of the characteristics of sports injuries, understanding the causes of sports injuries in current fitness exercises can provide an important reference basis for how to correctly deal with and prevent common sports injuries, and then improve the fitness consciousness of our people at the social level, and help the construction of a well-off society in an all-round way.